The origin and distribution of the main oxygen sensing mechanism across metazoans - Song, Bing; Modjewski, Luca David; Kapust, Nils; Mizrahi, Itzhak; Martin, William F. (Frontiers in Physiology, 2022)
Oxygen sensing mechanisms are essential for metazoans, their origin and evolution in the context of oxygen in earth history are of interest. To trace the evolution of a main oxygen sensing mechanism among metazoans, the hypoxia induced factor, HIF, we investigated the phylogenetic distribution and phylogeny of 11 of its components across 566 eukaryote genomes. The HIF based oxygen sensing machinery in eukaryotes can be traced as far back as 800 million years (Ma) ago, likely to the last metazoan common ancestor (LMCA), and arose at a time when the atmospheric oxygen content corresponded roughly to the Pasteur point, or roughly 1% of present atmospheric level (PAL). By the time of the Cambrian explosion (541 to 485 Ma) as oxygen levels started to approach those of the modern atmosphere, the HIF system with its key components HIF1A, HIF1B, PHD1, PHD4, FIH and VHL was well established across metazoan lineages. HIF1A is more widely distributed and therefore may have evolved earlier than HIF2A and HIF3A, and HIF1B and is more widely distributed than HIF2B in invertebrates. PHD1, PHD4, FIH, and VHL appear in all 13 metazoan phyla. The O2 consuming enzymes of the pathway, PHDs and FIH, have a lower substrate affinity, Km, for O2 than terminal oxidases in the mitochondrial respiratory chain, in line with their function as an environmental signal to switch to anaerobic energy metabolic pathways. The ancient HIF system has been conserved and widespread during the period when metazoans evolved and diversified together with O2 during earth history.